The elites of Ragusa were regarded very positively by the French administrators of the Illyrian Provinces (1809-1813). - Sajkowski, Wojciech (Balcanica Posnaniensia. Acta et studia, 2019)
With small exceptions, it is not possible to find in the remaining testimonies any traces of stereotypes that could be associated with the images of the Balkans, the Orient or Eastern Europe. Although the nobility of Ragusa was described as proud, this pride was presented as justified, because the bond of the most-important families with the republic reached back to the Middle Ages, and also because of the entrepreneurial spirit of the nobles that brought prosperity to the whole city. The picture was contrasted with the descriptions of Dalmatian Italians, portrayed as intruders who did not contribute to the development of the region. The difference between the perception of the Italian and Ragusan elite was connected with the concept of a nation that became one of the key elements of the Napoleonic policy in Europe.